Impact of Green Accounting & Corporate Social Responsibility on Financial Performance: A Systematic Literature Review - Dabbara Nurkayla Hufazsyah; Rika Henda Safitri; Emylia Yuniarti; Amirul Bahar (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study examined the impact of green accounting and corporate social responsibility on financial performance through a systematic literature review. Peer-reviewed articles published between 2020 and 2025 were screened and synthesized to assess how environmental accounting practices and social responsibility disclosure were associated with corporate financial outcomes. The review found that green accounting was linked to stronger financial performance, mainly through lower operating costs driven by resource efficiency and compliance with environmental regulations. Evidence on the direct effect of corporate social responsibility on financial performance was mixed. Several studies reported positive financial outcomes through improved corporate reputation and increased investor confidence, while other studies reported limited or no direct association. Legitimacy theory and stakeholder theory were used to interpret how transparency in environmental and social practices influenced financial performance. The synthesis indicated that integrated implementation of green accounting and corporate social responsibility supported financial stability and reputational outcomes, although the results varied by industry and depended on implementation quality and governance.